2021
DOI: 10.1073/pnas.2011196118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic basis for receptor-mediated pathological α-synuclein fibril cell-to-cell transmission in Parkinson's disease

Abstract: The spread of pathological α-synuclein (α-syn) is a crucial event in the progression of Parkinson’s disease (PD). Cell surface receptors such as lymphocyte activation gene 3 (LAG3) and amyloid precursor-like protein 1 (APLP1) can preferentially bind α-syn in the amyloid over monomeric state to initiate cell-to-cell transmission. However, the molecular mechanism underlying this selective binding is unknown. Here, we perform an array of biophysical experiments and reveal that LAG3 D1 and APLP1 E1 domains commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 59 publications
2
59
0
Order By: Relevance
“…Importantly, the reduction was non total, and in the same study Mao and coworkers revealed that the Ab precursor-like protein 1 (APLP1) also act as a receptor leading to the entry of αSyn fibrils [ 190 ]. In very recent work, Zhang and coworkers investigated in more detail the molecular mechanism underlying the selective binding of fibrillar αSyn to neuronal cells through Lag-3 and APLP1 receptors, revealing that the acidic C-terminus of αSyn, particularly exposed on the surface of fibrillar conformers, is the key domain binding to a positively charged surface on the analysed receptors [ 206 ]. Importantly, S129 phosphorylation of αSyn, a typical modification of pathological αSyn abundant in Lewy bodies and neurites, determines a significant increase in the binding of αSyn fibrils to the receptors, thus promoting their spreading, finally culminating in neurodegeneration [ 206 ].…”
Section: Fibril Spreadingmentioning
confidence: 99%
“…Importantly, the reduction was non total, and in the same study Mao and coworkers revealed that the Ab precursor-like protein 1 (APLP1) also act as a receptor leading to the entry of αSyn fibrils [ 190 ]. In very recent work, Zhang and coworkers investigated in more detail the molecular mechanism underlying the selective binding of fibrillar αSyn to neuronal cells through Lag-3 and APLP1 receptors, revealing that the acidic C-terminus of αSyn, particularly exposed on the surface of fibrillar conformers, is the key domain binding to a positively charged surface on the analysed receptors [ 206 ]. Importantly, S129 phosphorylation of αSyn, a typical modification of pathological αSyn abundant in Lewy bodies and neurites, determines a significant increase in the binding of αSyn fibrils to the receptors, thus promoting their spreading, finally culminating in neurodegeneration [ 206 ].…”
Section: Fibril Spreadingmentioning
confidence: 99%
“…Related to that, it is not surprising that α-Syn adopts a monomeric, random coil conformation in an aqueous medium, while its interaction with lipid membranes drives the transition of the protein part (N-terminus and NAC region) into defined α-helical structures ( Figure 1 ) [ 60 , 62 ]. The dynamic C-terminal part is involved in interactions with ligands (ions, polyanions, and polycations), protein partners, and membrane binding [ 24 , 68 ]. Within the C-terminal domain, residues 120–130 were shown to interact with residues 105–115, while positively charged N-terminal residues can interact with negatively charged C-terminal residues, forming a closed α-Syn conformational state [ 69 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Cell-to-cell transfer mediated by receptors, or the so-called ‘prion-like’ hypothesis, suggests that α-Syn oligomers can migrate between neurons [ 6 ]. Moreover, the acidic α-Syn C-terminus interacts with alkaline patches on the cell surface receptors, such as lymphocyte activation gene 3 (LAG3) and amyloid precursor-like protein 1 [ 68 ]. Amyloid fibril formation dramatically enhances (>200 times) binding to receptors due to the more accessible C-terminus that is shielded in the monomer.…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Phosphorylation at serine-129 was reported to induce the formation of distinct α-syn strains (14), and phosphorylated exogenous α-syn fibrils could exacerbate pathology and induce neuronal dysfunction in mice (15). A recent report also concluded that p-α-syn enhanced the interaction between αsyn fibrils and its receptors, which meant that p-α-syn could facilitate the spread of α-syn pathologies (16). Overall, the role of p-α-syn is relatively complicated, and further studies Abbreviations: α-syn, α-synuclein; AP, alkaline phosphatase; β-syn, β-synuclein; BCA, bicinchoninic acid; C, C-terminal domain of α-synuclein (residues 96-140); CBS, Coomassie Brilliant Blue staining; ELISA, enzyme-linked immunosorbent assay; h-α-syn, human α-synuclein; m-α-syn, mouse α-synuclein; MS, mass spectrometry; N, N-terminal domain of α-synuclein (N-α-syn, residues 1-60); N, N-terminal domain of α-synuclein; NAC, non-amyloid component, the central domain of α-synuclein (residues 61-95); p, phospho-group; p-α-syn, serine-129site phosphorylated α-synuclein; PD, Parkinson's disease; PFF, preformed fibrils; PLK3, Polo-Like-Kinase 3; pNPP, p-nitrophenyl phosphate; KO, α-syn knockout mice; R, rabbit; SD, standard deviation; SEM, standard error of the mean; TEM, transmission electron microscopy; Tg, Thy1-SNCA transgenic mice; ThT, thioflavin T; Wt, wild-type brood mice.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation at serine-129 was reported to induce the formation of distinct α-syn strains ( 14 ), and phosphorylated exogenous α-syn fibrils could exacerbate pathology and induce neuronal dysfunction in mice ( 15 ). A recent report also concluded that p-α-syn enhanced the interaction between α-syn fibrils and its receptors, which meant that p-α-syn could facilitate the spread of α-syn pathologies ( 16 ). Overall, the role of p-α-syn is relatively complicated, and further studies are still needed to reveal its exact mechanism involved in PD pathologies.…”
Section: Introductionmentioning
confidence: 99%